Methodology and methods: the difference between tools and interpretive frameworks and what this means in practice - Brænder, Morten (Politica, 2022)
The purpose of this article is two-fold. First, it introduces the distinction between methods and methodology. Second, it briefly describes the three methodologies prevailing within the social sciences: the variance-oriented, the process-oriented and the meaning-oriented methodology. These are illustrated with a recurring example. Methods are tools. They may be qualitative or quantitative. Methodologies are interpretive frameworks, best understood as languages. As you cannot expect to be understood in another language if you translate word by word, you cannot transfer the underlying logic from one methodology to another. Notably, this does not imply that translations are impossible, but that it is extremely difficult to translate without recognizing linguistic or – as in this case – methodological differences.